SediRate‐Fischer plots as a tool to illustrate relative sea‐level and lake‐level changes in subaqueous terrigenous deposits. Issue 5 (25th March 2022) - Yang, Daming; Huang, Yongjian; Wang, Chengshan
Abstract: For more extensive and efficient sea‐level and lake‐level reconstructions and correlations in siliciclastic systems, this paper presents a new tool called SediRate‐Fischer plot (SR‐Fischer plot). In SR‐Fischer plots, the linear‐corrected sedimentary rate of each terrigenous sedimentary cycle is plotted from the top of the previous cycle to the top of the current cycle. This process is repeated cycle by cycle, constructing curves of cumulative departure from mean sedimentary rate (CDMR). Based on the assumption that relative sea‐level and lake‐level changes may control sedimentary rates of subaqueous terrigenous sediments within basins, the CDMR could change inversely with relative sea or lake level. Thus, this tool could be interpreted as an indicator of relative sea‐level and lake‐level changes in terrigenous successions. SediRate‐Fischer plots can be obtained from either lithological or proxy cycles formed by sea‐level and lake‐level changes in the case of availability of orbitally tuned data. The SR‐Fischer plots constructed based on different materials are compared with other methods in two cases, as follows: first for the lacustrine Mingshui Formation of the Songliao Basin in China; and second for the deep‐marine Arcillas de Gibraleón Formation of the Guadalquivir Basin in Spain. The SR‐Fischer plots of the Mingshui Formation exhibit low and high CDMR values for shallow‐lake intervals and lakeshore intervals, respectively, and vary inversely with the lake‐level curves derived from changes in sedimentary facies. For the Arcillas de Gibraleón Formation, the CDMR values illustrated by the SR‐Fischer plots exhibit opposite variations with sea‐level curves indicated by dinocyst/pollen ratios. The negative Z ‐scores derived from runs tests indicate that these SR‐Fischer plots are not randomly stacked and are minimally influenced by different cycle‐splitting strategies. Thus, the results of comparison with other methods and runs tests demonstrate the validity of this method. Nonetheless, the other allogenic inflows (tectonics and climates) may limit interpretations of SR‐Fischer plots.